Evaluation of long-term results of surgical treatment of patients with hiatal hernia by the method of daily pH-metry - S. V. Dergal'; V. K. Koryttsev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
A comparative assessment of the long-term results of surgical treatment of patients with hernia of the esophageal opening of the diaphragm was made. All patients were divided into two groups. The first group included patients who underwent isolated correction of a hernia of the esophageal orifice of the diaphragm. Patients of the second group, in addition to correcting a hernia of the esophageal orifice of the diaphragm, performed simultaneous operations depending on the concomitant pathology in the abdominal cavity. The results of surgical treatment were evaluated using the method of daily pH-metry. It is concluded that performing simultaneous operations in patients with hernia of the esophageal orifice of the diaphragm is justified.